PHILOSOPHICAL FOUNDATION OF TEACHING AS A PROFESSION AND ITS IMPLICATION ON TEACHER EDUCATION - Soedijarto, Soedijarto (International Journal of Education, 2010)
suggesting its implication on the program of teacher education in Indonesia. A history of teacher education is described in the first discussion to provide a background for the idea of teaching as professional occupation. The history of teacher education starting from Ducth colonial era until the Education Law on Teacher and Lecturer number 14 Year 2005 prevailed has a complex dynamic where teachers’ qualifications before the education law existed were various. The Education law makes teachers’ qualifications more homogenous where it states that a teacher needs to have a full bachelor degree (S1) or at least diploma IV. The demand of law is reasonable because teachers’ role and responsibility are very challenging. In accordance with this, the philosophical foundation of teaching as a profession is to achieve education missions to support existence of a modern and democratic country of Indonesia based on Pancasila. It means that teachers need to be competent enough to develop competences and mould character of students based on stated competence standards. Competent teachers have to be able to arrange instructional planning, to design instructional program, to manage instructional processes, to evaluate instructional processes and achievement, to diagnose learning difficulties, to encourage and to motivate learners. To be competent teachers, they need to accomplish three stages of teacher education and training, namely: 1) academic professional education; 2) professional education and training; 3) practical professional training.